Analisis Kesulitan Siswa Dalam Menyelesaikan Masalah Matematika Materi Sistem Persamaan Linear Dua Variabel Ditinjau Dari Kesadaran Metakognisi - Asmira Sudiman (Peneliti.net, 2022)
This study aims to determine the description of students' difficulties in solving two-variable systems of linear equations problems in terms of metacognition awareness and the factors that influence students' difficulties in solving two-variable systems of linear equations problems. This research is a qualitative research using a descriptive approach. Subject collection was carried out by giving metacognitive awareness questionnaires to class VII students of SMP Negeri 4 North Halmahera. From these results, 3 subjects were purposively selected based on categories, namely subjects with high metacognitive awareness, subjects with moderate metacognitive awareness and subjects with low metacognitive awareness. The instruments used were the Metacognitive Awareness Inventory (MAI) questionnaire developed by Scraw & Dennison which contained 30 statement items, a diagnostic test for the difficulty of solving a two-variable linear equation system problem which contained 2 item description questions and an interview guide. Problem solving difficulties were analyzed based on Polya's problem solving steps, namely difficulty understanding the problem, difficulty thinking of plans, difficulty implementing plans and difficulty reviewing. The results showed: 1) Subjects with high metacognitive awareness only found it difficult to understand the problems in word problems. 2) Subjects with metacognitive awareness are experiencing three difficulties in solving real problems related to the two-variable linear equation system material, namely difficulty thinking of plans, difficulty implementing plans and difficulty reviewing. 3) Subjects with low metacognitive awareness experience the most difficulty in solving problems of systems of two-variable linear equations. Subjects experienced four types of difficulties, namely difficulty understanding the problem, difficulty thinking of plans, difficulty implementing plans and difficulty reviewing.